Strategi Pengurangan Risiko Kerusakan Pada Komponen Kritis Boiler di Industri Pembangkit Listrik - Iing Pamungkas; Heri Tri Irawan (Jurnal Optimalisasi, 2020)
This paper uses the failure mode approach and effect analysis (FMEA) in formulating a risk reduction strategy for damage to critical components of the boiler section of the Nagan Raya steam power plant. Boilers are an important part of the production system of steam power plants. The problem in the boiler section is the relatively high damage frequency compared to other parts. The aim of this study is to propose a risk reduction strategy for critical boiler components using a failure mode approach and effect analysis (FMEA). The proposed damage risk reduction will prioritize important components that have the highest risk priority number (RPN). The strategy that was successfully formulated was for the cyclone separator component, to carry out periodic and scheduled preventive checks and maintenance, especially on the return leg to prevent the accumulation of solid particles in the fluid system. Primary air fans and induced draft fan components, they must perform standard operational procedures (SOP) when operating the fan so that they do not experience high vibrations, and routinely balance the rotor contained in the fan. As for the coal feeder components, monitor the coal flow in detail so that it does not accumulate at one particular point, which can cause leakage at the outlet flanges.